2002
DOI: 10.1046/j.1365-2559.2002.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast hamartomas: clinicopathological and immunohistochemical studies of 24 cases

Abstract: There was no association with side, ethnic origin or dietary habits. The immunohistochemistry of hamartomas is generally similar to normal breast or fibrocystic breast tissue. Ki67 together with receptor positivity may reflect some proliferative activity and explain observed faster growth of hamartoma during pregnancy and lactation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 15 publications
1
50
0
1
Order By: Relevance
“…In total, 27 hamartomas (3.1%) were diagnosed among 864 benign breast tumors at our center over the last ten years. In the literature (23,28,29,31,33,34,37), the average age of the patients with breast hamartoma ranged between 33.5 and 66.5 years. In our study, the age range was from 19-56 years and the mean age was 41.8 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 27 hamartomas (3.1%) were diagnosed among 864 benign breast tumors at our center over the last ten years. In the literature (23,28,29,31,33,34,37), the average age of the patients with breast hamartoma ranged between 33.5 and 66.5 years. In our study, the age range was from 19-56 years and the mean age was 41.8 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, female sex steroid hormones (34) have been implicated in the development of breast hamartomas. In one study, Herbert et al (33) reported estrogen receptor (ER) and progesterone receptor (PR) positivity in epithelial cells and stromal cells in all 24 cases with breast hamartomas. Additionally, there are no clear data on the source of smooth muscle for myoid hamartomas, but this muscle could derive from vessels, the nipples, undifferentiated breast stromal tissue or myoepithelial cells (4,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,8] Adipose tissue within the stroma is also commonly reported in hamartomas. In most series, [2,3,5,6] adipose tissue is present in more than 90% of the cases. In the present study we found adipose tissue to be present in all the cases similar to the study of Tse, Law, Ma, et al [7] McGuire et al and Jones et al have classified hamartomas of the breast based on fibrous and adipocytic components.…”
Section: Resultsmentioning
confidence: 99%
“…3 To the best of our knowledge, only four studies of FNA cytology have been reported. [4][5][6][7] The aim of this study was to determine if it is possible to distinguish hamartoma of the breast from fibroadenoma using the cytological features in FNA material.…”
mentioning
confidence: 99%